G1/S restriction point coordinates phasic gene expression and cell differentiation - Brian DeVeale; Leqian Liu; Ryan Boileau; Jennifer Swindlehurst-Chan; Bryan Marsh; Jacob W. Freimer; Adam Abate; Robert Blelloch (Nature Communications, 2022)
Somatic cells display phasic gene expression with compartmentalized gene expression during the cell cycle, while pluripotent cells lack phasic expression. Here, the authors describe a pathway linking microRNA regulation of the G1/S restriction point with phasic gene expression and cell differentiation during mammalian development.